Application Of Six-Sigma Techniques To Human Capital Management In Hotels# ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Six-Sigma is a quality improvement strategy that provides a clear roadmap for  organizations to deliver nearly perfect products and services. In an increasingly knowledge intensive  and global economy, superior management of human capital- the skills, talents and knowledge of  an organisation’s employees is arguably the only sustainable source of competitive advantage for  an organisation. Objective: To assess the effectiveness of Six-Sigma and examine its impacts on  various performance measures in hotels, seeking for what values and benefits it brings to improve  the overall performance of human capital. Methodology: The survey was circulated to a panel of  prominent academics and Hotel professionals in the field of quality management to capture their  feedback as a part of a pilot survey. The respondents were asked to rank the 10 key drivers needed  for the successful deployment of Six-Sigma on a scale of 1-5 Results: Only 31% of these hotels  were actively involved in a documented Six-Sigma project. Four hotels are planning to implement  Six-Sigma in the near future. The results of the study also revealed that the most commonly used  Six-Sigma metrics is the number of customers’ complaints. This metric is followed by defect rate and  process capability. Human Capital Performance scores give an indication that hotels implementing  Six-Sigma have achieved more benefits as compared to other hotels implementing other quality  management programs. Conclusion: Six Sigma need to well propagate among hospitality sector so  that its benefits can help improve customer satisfaction.
Keywords: Six-Sigma; Strategic HRM; Human Capital; Intangible; Analytic; Alignment